2009
DOI: 10.1007/s10554-009-9550-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of subclinical left ventricular dysfunction with longitudinal two-dimensional strain and strain rate imaging in patients with mitral stenosis

Abstract: Longitudinal two-dimensional strain deformation is a novel technique which evaluates global and regional left ventricular (LV) function with high reproducibility. The aim of the study was to investigate the global and regional systolic function using this method in patients with pure mitral stenosis (MS). Conventional echocardiography and longitudinal two-dimensional strain analysis were performed in 60 patients (41 +/- 5 years, 48 women) with mild to moderate MS (mitral valve area: 1.9 +/- 0.5 cm(2)), and 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…Examples include ischemic/non-ischemic cardiomyopathy [23] and hypertrophic cardiomyopathy [24]. However, there is only one 2D strain imaging study in the literature related to MS [18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include ischemic/non-ischemic cardiomyopathy [23] and hypertrophic cardiomyopathy [24]. However, there is only one 2D strain imaging study in the literature related to MS [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In the diagnosis of LV dysfunction due to MS, some studies have shown EF, TDI, and Doppler strain to be useful [14,15,16,17]. However, studies related to the use of 2D strain, a more objective technique in the diagnosis of LV systolic function in MS, are very limited [18]. In this study, we aimed to evaluate the role of 2D strain in the assessment of subclinical LV systolic dysfunction and the relationship between stenosis severity and LV dysfunction in patients with MS.…”
Section: Introductionmentioning
confidence: 99%
“…30 Consequent to these changes (structural remodeling), the atrial myocytes lose their normal contraction and relaxation functions. 31 Hemodynamically, narrowing of mitral orifice poses increased resistance to LA emptying i.e. increased LA afterload.…”
Section: Discussionmentioning
confidence: 99%
“…Özdemir et al (11) determined subclinical insufficiency in all of the basal segments and some of the mid segments in 60 patients with mild-moderate mitral stenosis. However, in that study, measurements were taken differently via average global longitudinal strain and strain rate imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…While SE is affected by preload and heart rate, SRE shows parallelism to inotropic conditions and contractility, independently from the loading conditions (7,8). Recently, it was reported in several studies that, subclinical LV dysfunction was demonstrated via that imaging methods in patients having pure mitral stenosis and normal LV function with traditional echocardiography (9)(10)(11). In these studies, commonly, particular segments of LV were evaluated.…”
Section: Introductionmentioning
confidence: 99%